KEUNIKAN DAN KEARIFAN LOKAL ALUN-ALUN SURYAKENCANA SEBAGAI PENDAPATAN WISATA DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO (TNGGP) - Yuri Rahayu; Yulianto Yulianto; Saeful Bahri (STIE Pariwisata API Yogyakarta, 2019)
Local wisdom is the protection, environmental management in the effort to preserve and preserve the original culture and environment by using the common sense of the people (cognition) in shaping the social institution among local and surrounding residents who sometimes Neglected even in the damaged by humans. In fact, local wisdom can be a proof of history that can be preserved. The research methods used are qualitative researchers. Research that obtained data not